2022
DOI: 10.3389/fmed.2021.800180
|View full text |Cite
|
Sign up to set email alerts
|

Single-Port Laparoscopic Surgery for Adnexal Mass Removal During Pregnancy: The Initial Experience of a Single Institute

Abstract: ObjectiveSingle-port laparoscopy has become a feasible and safe approach for the management of benign adnexal masses during pregnancy. To our knowledge, there are few reports on the feasibility and safety of single-port laparoscopy for adnexal mass removal during pregnancy. Our study reports the use of single-port laparoscopy in adnexal mass removal during pregnancy in our hospital.MethodsWe included 10 cases of single-port laparoscopic surgery for adnexal mass removal during pregnancy in the West China Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…LESS surgery, in which surgical manipulation is performed through a single incision in the umbilical region, has been introduced to provide further benefits of the laparoscopic approach to adnexal disease in pregnant women [ 7 , 11 , 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LESS surgery, in which surgical manipulation is performed through a single incision in the umbilical region, has been introduced to provide further benefits of the laparoscopic approach to adnexal disease in pregnant women [ 7 , 11 , 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potential advantages of LESS surgery over conventional multiport laparoscopy include avoiding the risk of injury due to improper penetration of the enlarged uterus during insertion of an insufflation needle or trocar because the working port is created in the umbilicus by an open method under direct observation instead of closed puncture. Additionally, reducing the number of ports can minimize abdominal wall trauma [ 7 , 11 , 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were previously reported studies in this topic [5][6][7], but still concerns were found for evaluating roles of SPL surgery in management of benign adnexal masses during pregnancy [8].…”
Section: Introductionmentioning
confidence: 99%
“…This scenario is frequently a diagnostic source issues, which can lead to incorrect surgical therapy [8]. Aside from an emergency, conservative therapy is addressed; nevertheless, the advent of appendix torsion and other acute complications necessitates relatively hostile surgical methods [9].…”
Section: Introductionmentioning
confidence: 99%